Evaluasi Pemanfaatan Zonasi TPA Tamangapa Kota Makassar - Andi Ike Nurjannah; Muhammad Fathien Azmy; Yashinta Kumala Dewi Sutopo (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2017)
Makassar City Tamangapa Landfill is one of the crucial infrastructures, but its management is neglected so that it requires serious handling. This study aims to determine the existing conditions of each zoning utilization and the direction of sustainable zoning utilization. The analytical method used is descriptive and quantitative evaluation criteria analysis using a comparative method between existing and ideal conditions which is then weighted, spatial analysis consisting of proximity and superimpose analysis. The results of the analysis show that the Tamangapa landfill zoning utilization as a whole is included in the "enough" category with a percentage of 41.32% fulfilling the ideal zoning utilization rules, this result is obtained from the average percentage of each criterion namely zonation determination criteria (16.6%), criteria subzone distance (65.7%), spatial planning technical criteria (50.18%) and risk index criteria (32.8%). The direction of utilization is based on the best practice of utilizing TPA zoning which refers to the development of sustainable development values, namely environmental, social and economic.